Beyond Technocracy: A Sufi-Maqasid Epistemological Synthesis for the Kurikulum Berbasis Cinta (KBC) in Islamic Education - M Isroul Laili; Ahmad Burhan Jazuli; Muhammad Fodhil; Moh Saiful Mustofa; Luthfi; Ahmad Thohir; Imad Syauqi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The accelerating dominance of technocratic rationality and performative accountability within contemporary education has generated profound concern regarding the erosion of spirituality, ethical consciousness, and holistic human formation in Islamic educational institutions. Although the Indonesian Ministry of Religious Affairs introduced the Kurikulum Berbasis Cinta (KBC) as a transformative curriculum initiative intended to restore compassion, relationality, and human-centered learning, the curriculum remains epistemologically fragile due to the absence of a coherent philosophical framework integrating spirituality, ethics, cognition, and transformative pedagogy. Addressing this gap, the present study develops a Sufi-Maqasid Epistemological Synthesis Model (SM-ESM) as a post-technocratic curriculum architecture for contemporary Islamic education. Employing a qualitative conceptual-hermeneutic design grounded in critical Islamic educational philosophy, the study analysed classical Islamic texts, contemporary scholarly literature, and official KBC policy documents through purposive and criterion-based selection. The findings reveal that the integration of Sufi epistemology and Maqasid al-Shariah systems thinking reconstructs the epistemological foundations of Islamic curriculum discourse by positioning love not merely as an affective value, but as an ontological, ethical, and pedagogical principle governing knowledge, human flourishing, and educational purpose. The study further demonstrates that the tri-yaqin epistemological ascent fundamentally redefines Higher Order Thinking Skills (HOTS) through the integration of conceptual understanding, reflective awareness, and ethical-spiritual embodiment oriented toward ihsan-consciousness. Moreover, the alignment between the Panca Cinta principles and Maqasid al-Shariah establishes a coherent teleological framework capable of resisting reductionist educational instrumentalism while strengthening transformative pedagogy, ecological responsibility, and relational ethics. Ultimately, this study positions Islamic educational philosophy as a globally relevant alternative paradigm for reconstructing spiritually grounded, human-centered, and ethically transformative education within an increasingly performative post-technocratic world.